PEMERTAHANAN BAHASA BALI DI ERA DIGITAL: PERAN DAN HUMOR DALAM KARTUN KUMARA - Anggreni, Ni Putu Dewi; Taruna, Made Krismantara Putra Adi; Sidemen, Ida Bagus Aswinda Eka Temaja (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
Balinese is one of the regional languages in Indonesia that faces significant challenges in the digital era of globalization. Amid the onslaught of foreign languages easily entering through digital media, this actually presents a great opportunity for the Balinese language as well, because it can also empower and utilize the way foreign languages spread. Through various efforts, content about preserving of the Balinese Language has emerged, both in the form of education, news, and entertainment. This research aims to explore the role of the Kumara cartoon in preserving, maintaining, educating, and introducing the Balinese language using digital media. In order to strengthen that role, light humor is incorporated to enhance the appeal of Kumara's content for all audiences. This research aims to explore the role of humor in the Kumara cartoon as a medium for the preservation and revitalization of the Balinese language amidst the development of digital technology. Using the Role and Humor theory, this research analyzes how humor functions as an effective tool in attracting the audience's attention, especially the younger generation, and conveying cultural messages and local values. Research data were collected using the observation method, with a non-participant observation model, presented using deductive techniques. The research results reveal that Kumara effectively fulfills the intended role in the context of preserving, maintaining, educating, and introducing the Balinese language using digital media, complemented by various humor that not only entertains but also introduces and popularizes the Balinese language among the wider community. Humor is able to ease the tension of a language that is often considered difficult and build a strong emotional connection with the audience. This research confirms that entertainment content using digital media can be an effective strategy in the preservation of the Balinese language.